CRISPR/Cas9 Mediated Deletion of the Angiotensinogen Gene Reduces Hypertension: A Potential for Cure?. Issue 6 (5th April 2021) - Sun, Hualing; Hodgkinson, Conrad P.; Pratt, Richard E.; Dzau, Victor J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Hypertension is a major contributor to the global burden of disease. Unfortunately, hypertension is controlled in less than one-fifth of patients worldwide due to either failure to treat or lack of compliance to medication. An ideal therapy would be administered one time only and yield lifelong blood pressure control. We investigated our hypothesis that CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat–associated 9)-mediated disruption of a key gene in the renin-angiotensin system, AGT (angiotensinogen), specifically in the liver, would result in sustained and possibly lifelong reduction in blood pressure. We demonstrated in vitro that the CRISPR/Cas9 system led to a significant reduction in AGT expression in hepatocytes. Delivery of the CRISPR/Cas9 system into the liver via the hepatocyte-targeting adeno-associated virus 8 reduced both AGT expression (40% decrease) and circulating AGT levels (30% decrease). In the SHR (spontaneously hypertensive rat) model of hypertension, CRISPR/Cas9-mediated loss of AGT expression reduced blood pressure in adult animals with established hypertension and prevented the spontaneous development of hypertension in young SHR. Moreover, reductions in blood pressure were prolonged and sustained up to 1 year of follow-up. In addition, the partial disruption of the hepatic AGT gene was sufficient to control hypertension but did not affect the homeostatic response to cardiovascular stress such as sodium depletion and furosemide. In summary, we have demonstrated that targeting the CRISPR/Cas9 system to hepatic AGT results in sustained reduction of blood pressure and is a potential therapy to achieve sustained and possibly lifelong control of human hypertension.